Why Principals Leave? Why Principals Stay? - Burress, Karen Conner (The University of North Carolina at Greensboro, 2017)
The purpose of this study was to investigate principal turnover to determine the perceived reasons why principals leave their positions, or why they stay. My study addressed the experiences of those individuals, telling their stories of why they leave their assigned schools, including their needs and stressors, or describing their external supports they perceive causing them to stay. The qualitative study borrowed elements of a narrative study through the interview process. Nine current or former administrators, in two Piedmont North Carolina school districts, were selected for interviews, lasting approximately 90 minutes to two hours in length. All interviews were conducted at the convenience of the school employee in relation to time and location. The participants represented a cross section of experience, levels of schooling, gender and ethnicity. The significance of their experiences as it relates to principal retention and turnover were examined. The major stressors identified were raising achievement scores and lack of support from supervisors. The supports of having effective mentors and instructional coaches, being able to distribute leadership and having valuable college coursework were common among participants. Other major themes included the importance of finding balance in the principalship, the impact of health issues, the rewards of being a school leader and advice they would give to new administrators. Current and future principals, policy makers and school districts can benefit from the data gathered as it relates to the needed skill sets, supports and stressors to promote less turnover in the principalship.